2020
DOI: 10.1021/acsami.0c20404
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Mesoporous Adsorption Channels and MOF–Polymer Interfaces in Electrospun Composite Fibers for Effective Removal of Emerging Organic Contaminants

Abstract: Recently, metal–organic framework (MOF)-based electrospun fibers have attracted considerable attention as adsorbents for organic contaminant removal from water. To prepare these fibers, two common strategies including blending electrospinning and surface coating are employed. However, fibers obtained from the two strategies still have some disadvantages, such as adsorption site blockage and unstable loading. Here, we constructed interconnected mesopores in the electrospun zeolitic imidazolate framework-8 (ZIF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 49 publications
(70 reference statements)
0
45
0
Order By: Relevance
“…Meanwhile, the strong intermolecular connectivity through coordination bonds has granted MOFs with permanent porosity, a signature attribute of porous materials. Nevertheless, both crystallinity and permanent porosity come at a cost of losing the materials’ flexibility and processability, which are two essential qualities when it comes to many industrial applications. Therefore, MOF particles are often blended with soft polymers in the form of dense membranes, foams, fibers, and even fluids , to endow MOFs with improved processability. However, dispersing a rigid powdery substance into a soft polymeric medium often confronts a challenge of poor interfacial compatibility because of mechanical and chemical mismatch, which may lead to consequences such as interfacial defects, poor dispersibility, weakened mechanical strength, etc. …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the strong intermolecular connectivity through coordination bonds has granted MOFs with permanent porosity, a signature attribute of porous materials. Nevertheless, both crystallinity and permanent porosity come at a cost of losing the materials’ flexibility and processability, which are two essential qualities when it comes to many industrial applications. Therefore, MOF particles are often blended with soft polymers in the form of dense membranes, foams, fibers, and even fluids , to endow MOFs with improved processability. However, dispersing a rigid powdery substance into a soft polymeric medium often confronts a challenge of poor interfacial compatibility because of mechanical and chemical mismatch, which may lead to consequences such as interfacial defects, poor dispersibility, weakened mechanical strength, etc. …”
Section: Introductionmentioning
confidence: 99%
“…Adsorption [230] Fiber membrane with interconnected mesopores based on an electrospun zeolitic imidazolate framework-8 (ZIF-8)/PAN fibers integrated into PVP. Method: zinc salt and 2-methylimidazole as precursors into PVP to obtain electrospun fiber membrane, PVP removal at 50 Adsorption [236] Graphene oxide (GO)/poly(vinylidene fluoride) (PVDF) electrospun nanofibrous membranes (ENMs).…”
Section: Type Of Processmentioning
confidence: 99%
“…In addition, the mesopores enhanced the diffusion of pollutant molecules and created an MOF polymer interface in the fiber, which improved the adsorption rate and adsorption capacity, respectively. The fibers were used to adsorb tetracycline, an antibiotic, from water [ 36 ]. Maya et al demonstrated a general scheme for fabricating freestanding polymer fibers embedded in porous fibers, wherein the fibers themselves served as microreactors for the in situ growth of porous fiber crystals.…”
Section: Introductionmentioning
confidence: 99%